2014
DOI: 10.1158/0008-5472.can-13-1267
|View full text |Cite
|
Sign up to set email alerts
|

The CXCL7/CXCR1/2 Axis Is a Key Driver in the Growth of Clear Cell Renal Cell Carcinoma

Abstract: Mutations in the von Hippel-Lindau gene upregulate expression of the central angiogenic factor VEGF, which drives abnormal angiogenesis in clear cell renal cell carcinomas (ccRCC). However, the overexpression of VEGF in these tumors was not found to correlate with overall survival. Here, we show that the proangiogenic, proinflammatory cytokine CXCL7 is an independent prognostic factor for overall survival in this setting. CXCL7 antibodies strongly reduced the growth of ccRCC tumors in nude mice. Conversely, co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 48 publications
(70 reference statements)
1
87
0
Order By: Relevance
“…Inflammatory mediators are known to play crucial roles in tumor progression by regulating not just the immune infiltrations in tumors but also by playing the important role in invasion and metastasis [20, 21]. A number of studies have demonstrated that CXCR2 plays a pivotal role in tumor angiogenesis, proliferation, and invasion [8, 22, 23]. Up to now, however, the relationship between CXCR2 and miR-940 in HCC has been little noticed.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediators are known to play crucial roles in tumor progression by regulating not just the immune infiltrations in tumors but also by playing the important role in invasion and metastasis [20, 21]. A number of studies have demonstrated that CXCR2 plays a pivotal role in tumor angiogenesis, proliferation, and invasion [8, 22, 23]. Up to now, however, the relationship between CXCR2 and miR-940 in HCC has been little noticed.…”
Section: Discussionmentioning
confidence: 99%
“…In similar experiments, we showed that commercially available CXCL7 antibodies actually arrested tumor development 5 . On the other hand, tumors obtained with cells overexpressing CXCL7 grew more rapidly 5 .…”
mentioning
confidence: 57%
“…In similar experiments, we showed that commercially available CXCL7 antibodies actually arrested tumor development 5 . On the other hand, tumors obtained with cells overexpressing CXCL7 grew more rapidly 5 . However, extracts from experimental tumors contained high levels of human CXCL7 whereas the CXCL7 levels produced by the cultured cancer cell lines from which our xenograft models were derived were negligible.…”
mentioning
confidence: 61%
“…We previously described that redundant pro-angiogenic factors of the ELR+CXCL cytokine family played a key role in the mechanisms of resistance to BVZ in particular CXCL8 [13]. Moreover, we have also described that another member of these family of cytokines, CXCL7 is a marker of poor prognosis for RCC [24]. The production of both cytokines was thus tested in the cells derived from the different groups of tumors [25].…”
Section: Resultsmentioning
confidence: 99%